Performance of paddy straw mushroom under low-cost polyhouse conditions in winter - Pradhan, L; Nayak, M P (Mushroom Research, 2012)
Mushroom cultivation is considered to be a remunerative agro-based enterprise. The Agroclimatic conditions ofÂ Orissa are conducive for production of paddy straw mushroom during March to October and Oyster mushroom during November to February. As such, there is demand for paddy straw mushroom round the year. But its production is restricted due to low atmospheric temperature and humidity during winter months (November to February). The present study was undertaken in 3 villages namely Gopalpur in Bonth block, Jamojodi in Tihidi block and Radhaballavpur in Dhamnagar of Bhadrak district of Orissa to study the performance of paddy straw mushroom (Volvariella volvacea) under low cost polyhouse during winter months. Temperature, humidity and production were recorded at a fortnight interval. The average yield of paddy straw mushroom was 965 g per bed as against 1.5 kg during the peak season.Â